Percutaneous radiofrequency ablation for stage B1 of modified Bolondi’s subclassification for intermediate-stage hepatocellular carcinoma - Ragaey Ahmad Eid; Ali M. Abdel Fattah; Alaa Farouk Haseeb; Ahmed Moheyeldien Hamed; Marwa Abdallah Shaker (Egyptian Liver Journal)
Abstract Background Hepatocellular carcinoma is considered  the most common cause of hepatic focal lesions in Egypt. TACE is still the recommended treatment approach for patients in the intermediate stage. In the current research, we evaluated the safety and efficacy of percutaneous radiofrequency ablation (RFA) for a selected category in the intermediate stage (BCLC stage B). Methods This prospective study was conducted in the Department of Gastroenterology, Hepatology, Faculty of Medicine, Beni-Suef University between September 2022, and March 2024. In addition to AFP, Pelviabdominal ultrasound and computerized tomography (CT) were used for HCC diagnosis. According to the Child–Pugh score plus Milan and up-to-7 criteria, we used Modified Bolondi’s Subclassification (Kinki Criteria), to sub-classifies the BCLC B stage into B1/B2/B3 subcategories. Radiofrequency ablation was done in the interventional ultrasound unit. Treatment efficacy was assessed 6 months after tumor ablation. Results One hundred twenty participants were enrolled in our research trial, 72 (60%) were within the intermediate stage, and 48 (40%) had early-stage HCC. Most of our patients were males, 78 (65%). All the early-stage-HCC patients were Child–Pugh Score A (n = 48), while the intermediate-stage (BCLC B) group was classified in both Child–Pugh Score A (n = 59) and B (n = 16). Within the intermediate group (BCLC-stage B), All enrolled cases fell within category “B1” within the Kinki Criteria. Logistic regression analysis illustrated that the pre-treatment level of Platelet count and post-treatment level of AFP shows a statistically significant prediction effect on treatment response rate with p-value (0.028 and 0.007 respectively). Conclusion percutaneous radiofrequency ablation is considered an effective treatment option for the B1 subcategory according to Kinki Criteria for intermediate-stage HCC (BCLC-B1) but long-term follow-up is recommended.